Hepatocyte nuclear factor-4α and sex hormone-binding globulin levels in overweight polycystic ovary syndrome patients from the Babil Province - Hamza Abbas, Sheerin; Abbass Ali2, Zinah; Mohsen Najm, Zainab; Alshimary, Fatima (Pharmakeftiki, 2025)
Polycystic ovary syndrome (PCOS) is an endocrine condition that comprises two major elements: metabolic irregularities and elevated male hormone levels. Sex hormone binding-globulin (SHBG) acts as an essential androgen regulator; however, its expression and metabolic functions are controlled by the hepatocyte nuclear factor-4 alpha (HNF-4α). This study has investigated the relationship between the serum levels of SHBG and those of HNF-4α in overweight women with PCOS in the Babil Province of Iraq. To this end, we enrolled 45 women with PCOS (patient group) and a control group consisting of 45 participants. This study was conducted at the Babylon Teaching Hospital for Maternity and Children in Hilla City and at private clinics from May to December 2024. A microplate reader was used in order to determine the serum levels of glycated haemoglobin (HbA1c), SHBG, total testosterone, insulin, and HNF-4α. The PCOS group demonstrated significant elevations of serum HbA1c levels (p<0.05) together with higher serum testosterone (p<0.05), insulin (p<0.05) and HNF-4α (p<0.05) levels, as compared to those of the control group. The SHBG levels displayed a significant relationship with the HNF-4α levels in women with PCOS, thereby indicating that these markers may serve as metabolic regulators. Further studies are required in order to shed more light on both the biological processes and the potential treatment applications of our findings.